Solvothermal Synthesis and Crystal Structure of Cobalt(II) Complex Derived from 4-Heterocyclic Acylpyrazolone - Ding, Y.J.; Zhao, C.X. (Asian Journal of Chemistry, 2014)
A novel 4-acylpyrazolones complex of coblat [Co(CPTP)2(C2H5OH)2] (C2H5OH)2 (HCPTP = 1-(4-chlorophenyl)-3-phenyl-4-thenoyl-1H-pyrazol-5-ol) has been synthesized and characterized structurally. It crystallizes in the triclinic space group P-1 with a = 11.8582 (8), b = 14.2225 (9), c = 14.5396 (9) Å; a = 91.450 (2), b = 104.323 (2), g = 91.395 (2), V = 2374.0 (3) Å3, C14H20N2O18Co3, Mr = 1002.87, Z = 2, Dc = 1.403 g/cm3, m = 0.619 mm-1, F (000) = 1042, R = 0.0411 and wR = 0.1119 for 7780 observed reflections with I > 2s(I). The complex has a six-coordinated Co(II) center in a distorted octahedral configuration with two ethanol ligands in cis position. These octahedral units are connected through hydrogen bonds via two ethanol molecules along the c-axis.